TANGGUNG JAWAB BANK TERHADAP AGUNAN NASABAH DI BANK BTN KOTA KUPANG - Sulthanick Abizard; Yossie Maria Yulianty Jacob; Rini Marselin Kaesmetan (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Collateral management in credit agreements functions not only as a risk mitigation instrument for banks but also as an essential component of legal protection for customers' rights. Although previous studies have discussed bank liability in credit relationships, limited attention has been given to the implementation of bank responsibility for collateral from the binding process to the return of collateral documents. This study aims to analyze the collateral binding procedure in credit agreements and examine the forms of legal responsibility assumed by Bank BTN Kupang Branch toward customers' collateral. An empirical juridical approach was employed using primary data collected through interviews with two Bank BTN employees and five customers, supported by secondary data derived from statutory regulations and relevant literature. The data were analyzed qualitatively using an empirical juridical approach. The findings reveal that the collateral binding procedure consists of legal verification, document authentication, issuance of a covernote, and the establishment of security rights according to the characteristics of each credit product. The bank's responsibility is implemented through centralized document storage, supervision of notaries and developers under a Service Level Agreement (SLA), and the restoration of customers' rights when document loss or damage results from the bank's negligence. The study concludes that bank liability is not merely remedial after disputes arise but also preventive through the consistent implementation of the prudential principle and fiduciary principle from collateral binding, storage, and supervision to the return of collateral as a form of legal protection for customers.Keywords: collateral; bank liability; credit agreement; prudential principle; fiduciary principle.